2001
DOI: 10.1152/ajpregu.2001.280.4.r1045
|View full text |Cite
|
Sign up to set email alerts
|

Nonimmune hydrops fetalis and activation of the renin-angiotensin system after asphyxia in preterm fetal sheep

Abstract: This study examined the hypothesis that the development of hydrops fetalis after asphyxia in the 0.6 gestation sheep fetus would be associated with activation of the fetal renin-angiotensin system (RAS). Fetuses were randomly assigned to either sham occlusion (n = 7) or to 30 min of asphyxia induced by complete umbilical cord occlusion for 30 min (n = 8). Asphyxia led to severe bradycardia and hypotension that resolved after release of occlusion. After occlusion, plasma renin concentration was significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
2
20
1
1
Order By: Relevance
“…Alternatively, fetal hypoxia is associated with altered eNOS-dependent relaxation of umbilical vessels, with increased eNOS expression in umbilical arteries and reduced eNOS in the umbilical veins (Hracsko, et al, 2009), regulated at least in part by greater arginase-2 production in the umbilical venous circulation, reducing eNOS activity (Krause, et al, 2013). Further studies are needed to assess whether JI-10 could modulate these differential responses to hypoxia to alter the net hydrostatic pressure difference across the placenta and so promote fetal fluid accumulation (Lumbers, et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, fetal hypoxia is associated with altered eNOS-dependent relaxation of umbilical vessels, with increased eNOS expression in umbilical arteries and reduced eNOS in the umbilical veins (Hracsko, et al, 2009), regulated at least in part by greater arginase-2 production in the umbilical venous circulation, reducing eNOS activity (Krause, et al, 2013). Further studies are needed to assess whether JI-10 could modulate these differential responses to hypoxia to alter the net hydrostatic pressure difference across the placenta and so promote fetal fluid accumulation (Lumbers, et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Although it was not possible to evaluate myocardial histology and function directly in the present study, there is considerable clinical and experimental evidence to show that reversible myocardial injury and associated cardiac dysfunction are common during recovery from exposure to perinatal asphyxia (Gunn et al 2000; Lumbers et al 2001; Hunt & Osborn, 2002). Consistent with the hypothesis of early myocardial dysfunction, in the present study phentolamine infusion led to a reduction in blood pressure for 3–4 h despite normalization of SMA blood flow for most of this period.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, and consistent with previous studies of the renal responses to asphyxia at this gestational age (Quaedackers et al 2004 b ), we found marked initial hypertension during complete umbilical cord occlusion associated with an initial, actively mediated fall in FBF, as shown by the very rapid and large increase in vascular resistance in the first 6 min after the start of umbilical cord occlusion. In the near‐term fetus the initial vasoconstriction during asphyxia is primarily mediated by sympathetic neural activity (Jensen & Lang, 1992) and possibly augmented by release of stress hormones such as arginine vasopressin and renin–angiotensin system (RAS) activation (Raff et al 1991; Giussani et al 1994 b ; Rosnes et al 1998); limited data suggest that this also occurs in preterm fetuses (Cheung, 1992; Lumbers et al 2001). Finally, the rise in circulating cortisol demonstrated in the present study may also help to support initial hypertension, as discussed below.…”
Section: Discussionmentioning
confidence: 99%